Fabrication and characterization of nanostructured fluorine doped tin oxide thin film for dssc by hydrothermal method - Mohd Napi, Muhammad Luqman (2017)
Nanostructured Fluorine Doped Tin Oxide (FTO) thin film has been successfully synthesized on top of bare FTO layer substrates using hydrothermal method. The performance of FTO thin film including conductivity and transparency depend on the surface morphology and the properties of the material. Hydrothermal method has proven to be a very good method for the fabrication of novel metal oxides. Thus, a new nanostructured FTO thin film like nanorice has been fabricated using one step hydrothermal method. FTO nanorice thin films were obtained from the reaction of tin (iv) chloride (SnCl4), ammonium fluoride (NH4F), acetone, deionized water and hydrochloric acid (HCl). The compound was prepared in an autoclave at 150°C hydrothermal temperature for different reaction times of 5 hours, 10 hours, 15 hours, and 20 hours. FESEM studies on the surface morphologies of all the samples showed that nanorice structure had formed to fully cover the bare FTO substrate. Then, to further the optimization of FTO nanorice thin film, this research focused on studying the effect of hydrothermal temperature on FTO nanorice thin films. The experiments were conducted at 130°C, 140°C, 150°C, 160°C, and 170°C of hydrothermal temperature in constant reaction time of 10 hours. Basically, there were six properties studied; surface morphology, structural, element composition, thickness measurement, electrical and optical properties. At the end of this research, homogeneous FTO thin film has been successfully prepared. By controlling the reaction time and hydrothermal temperature, a transparent FTO film with beyond 85% percentage of transmittance was developed. The FTO thin film produced at 10 hour reaction time and 150°C of hydrothermal temperature time gave the low sheet resistance of 0.012 Ohm/sq with high transparency. The DSSC fabricated using the optimized FTO film gave higher efficiency of 2.77% compared to commercial FTO of 1.93%.